Apelin prevents diabetes-induced poor collateral vessel formation and blood flow reperfusion in ischemic limb - Robillard, Stéphanie; Trân, Kien; Lachance, Marie-Sophie; Brazeau, Tristan; Boisvert, Elizabeth; Lizotte, Farah; Auger-Messier, Mannix; Boudreault, Pierre-Luc; Marsault, Éric; Geraldes, Pedro (Frontiers in Cardiovascular Medicine, 2023)
Introduction Peripheral arterial disease (PAD) is a major risk factor for lower-extremity amputation in diabetic patients. Unfortunately, previous clinical studies investigating therapeutic angiogenesis using the vascular endothelial growth factor (VEGF) have shown disappointing results in diabetic patients, which evokes the necessity for novel therapeutic agents. The apelinergic system (APJ receptor/apelin) is highly upregulated under hypoxic condition and acts as an activator of angiogenesis. Apelin treatment improves revascularization in nondiabetic models of ischemia, however, its role on angiogenesis in diabetic conditions remains poorly investigated. This study explored the impact of Pyr-apelin-13 in endothelial cell function and diabetic mouse model of hindlimb ischemia. Methods Nondiabetic and diabetic mice underwent femoral artery ligation to induce limb ischemia. Diabetic mice were implanted subcutaneously with osmotic pumps delivering Pyr-apelin-13 for 28 days. Blood flow reperfusion was measured for 4 weeks post-surgery and exercise willingness was assessed with voluntary wheels. In vitro, bovine aortic endothelial cells (BAECs) were exposed to normal (NG) or high glucose (HG) levels and hypoxia. Cell migration, proliferation and tube formation assays were performed following either VEGF or Pyr-apelin-13 stimulation. Results and Discussion Following limb ischemia, blood flow reperfusion, functional recovery of the limb and vascular density were improved in diabetic mice receiving Pyr-apelin-13 compared to untreated diabetic mice. In cultured BAECs, exposure to HG concentrations and hypoxia reduced VEGF proangiogenic actions, whereas apelin proangiogenic effects remained unaltered. Pyr-apelin-13 induced its proangiogenic actions through Akt/AMPK/eNOS and RhoA/ROCK signaling pathways under both NG or HG concentrations and hypoxia exposure. Our results identified the apelinergic system as a potential therapeutic target for angiogenic therapy in diabetic patients with PAD.